The Boma: Why One Health matters - International Livestock Research Institute (International Livestock Research Institute, 2021)
One Health is traditionally defined as the collaboration of several disciplines working locally, nationally and globally to attain optimal health for people, animals, and the environment -- but what exactly does this mean, and what does it look like in practice? Today’s episode of The Boma features food expert Hung Nguyen, co-leader of the Animal and Human Health Program at ILRI. Hung takes us through how his childhood in a rural area of north Vietnam sparked his interest in livestock, public health, and then One Health. One of the challenges to the One Health approach remains the collaboration of different sectors, something that Vietnam has been unusually successful at managing. Hung provides insight into Vietnam as a case study for successfully integrating One Health, and One Health as a core consideration for global health concerns.